Relation between left ventricular contractile reserve during low dose dobutamine echocardiography and plasma concentrations of natriuretic peptides. Issue 3 (13th February 2004) - Schinkel, A F L; Vourvouri, E C; Bax, J J; Boomsma, F; Bountioukos, M; Rizzello, V; Biagini, E; Agricola, E; Elhendy, A; Roelandt, J R T C; Poldermans, D
Abstract : Background: In ischaemic cardiomyopathy, raised plasma concentrations of natriuretic peptides are associated with a poor long term prognosis, while the presence of contractile reserve is a favourable sign. Objective: To assess the relation between plasma natriuretic peptides and contractile reserve. Design: Prospective observational study. Setting: Tertiary referral centre. Patients: 66 consecutive patients undergoing low dose dobutamine stress echocardiography to evaluate contractile reserve in regions with contractile dysfunction at rest, divided into two groups: group 1, 31 patients with ischaemic cardiomyopathy (left ventricular ejection fraction ⩽ 40%) and heart failure symptoms; group 2, 35 patients with normal left ventricular function. Main outcome measures: Plasma atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), measured using immunoradiometric assays. Contractile reserve was defined as an improvement in segmental wall motion score during infusion of low dose dobutamine. Results: Plasma ANP and BNP concentrations were higher in group 1 than in group 2 (mean (SD): ANP, 17.8 (32.8) v 7.2 (9.7), p < 0.005; BNP, 24.4 (69.0) v 5.0 (14.3) pmol/l, respectively; p < 0.001). In group 1, the presence of contractile reserve was inversely related to ANP and BNP levels; however, patients with contractile reserve had lower ANP and BNP concentrations than patients without contractile reserve (ANP, 14.2 (9.1) v 24.2 (44.2), p < 0.05; BNP, 20.2 (25.5) v 37.5 (93.8) pmol/l, respectively; p < 0.05). Conclusions: Plasma natriuretic peptide concentrations are raised in patients with left ventricular dysfunction, but in the presence of preserved myocardial contractile reserve, relatively low levels of ANP and BNP are present.